SITUATION OF PRESCHOOL EDUCATIONAL INSTITUTIONS IN THE NEW UZBEKISTAN PERIOD - Norbotayeva Gozal Abdigafirovna (American Journals Publishing, 2024)
This article talks about the state of school educational institutions in the era of New Uzbekistan. The author, relying on scientific data, studied and analyzed the specific aspects of the state of school educational institutions in the period of New Uzbekistan based on available literature.
Keywords: New Uzbekistan, preschool education, institution, legal basis, material and technical base.